HUBUNGAN KECUKUPAN ENERGI, STATUS GIZI, BEBAN KERJA DENGAN KEJADIAN KELELAHAN KERJA (WORK FATIGUE) PADA PEKERJA DI JASA EKSPEDISI KOTA DENPASAR SELAMA PANDEMI COVID-19 - Wahyuni, Kadek Candra Dwi; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022DO - 10.24843/ACH.2022.v09.i01.p05, 2022)
The high demand for delivery of goods from online shopping activities carried out by the public due to restrictions on activities during the Covid-19 pandemic certainly affects expedition services, especially couriers to experience work fatigue. Work fatigue can be influenced by energy sufficiency, nutritional status, and workload. The purpose of this study was to determine the relationship between adequacy of energy sufficiency, nutritional status, workload with the incidence of work fatigue in workers in Denpasar City expedition services during the Covid-19 pandemic. Quantitative research design with approach cross sectional. The research sample was all couriers on two selected expedition services with a total of 115 respondents, the sampling technique used was the total sampling method. The result showed that 93,91% of couriers experienced mild fatigue, had normal nutritional status (81,74%), lacked energy sufficiency (86,94%), and light workload (93,04%). Bivariable test showed there was no relationship between energy sufficiency and work fatigue (p = 0.290), but there was a relationship between nutritional status and workload to the experience of work fatigue (p = 0.000). Suggestions in this study for couriers service to pays attention to health by eating varied foods, maintaining ideal body weight, and taking overtime capacity to be more scheduled. Keywords : Work Fatigue, Energy Sufficiency, Nutritional Status, Workload